Reflections on the responsibility of a collective being - Filek, Janina (Journal of Public Governance, 2014)
The main objective of the paper is to address the problem of responsibility of a collective being. This task has proven to be very complex due to the conviction which is currently dominant (in legal, political and economic consciousness): that of absolutely fundamental individual responsibility that closes any reflection on the responsibility of a collective being which could destroy one of the undoubtedly most valuable achievements of human thought: the idea of moral responsibility of a human being. However, the increasingly rapid changes both in the nature and structure of societies, and in social relations, which are its new face, show that with the increasing impact and power of large organizations (public and private alike), one has to refl ect on a new dimension of responsibility, i.e. the responsibility of a collective being. The paper is therefore an attempt to show research directions of the new phenomenon, without questioning the inviolability of individual responsibility.